The Effect of a Single Session of Transcranial Direct Current Stimulation on Attention in Pediatric Acquired Brain Injury: Characterizing Interindividual Structural and Functional Network Response Variability - Stein, Athena; Caulfield, Kevin A.; Singh, Mervyn; Riddle, Justin; Friehs, Maximilian A.; Craven, Michael P.; Groom, Madeleine J.; Iyer, Kartik K.; Barlow, Karen M. (Pediatric neurology, 2025)
Approximately one in four children who sustain an acquired brain injury (ABI) have attention difficulties impacting education, employment, and community participation. These difficulties arise from dysfunction in attention-related brain networks, incentivizing the use of transcranial direct current stimulation (tDCS). We investigated whether a single tDCS session improved attention following childhood ABI and whether baseline structural connectivity (sc), functional connectivity (fc), attention, and/or simulated electric fields (E-fields) explained variability in response. In a randomized, single-blind, within-subject, sham-controlled trial, 15 children with ABI (mean 12.7 years) and 15 healthy controls (HCs) received three single tDCS sessions (1 mA dorsolateral prefrontal cortex [dlPFC], 1 mA inferior frontal gyrus [IFG], sham; 20 min) during gamified attention training. We examined postintervention changes in attention according to flanker and stop signal reaction time (RT). We used multimodal analyses (high-density electroencephalography [HD-EEG], diffusion tensor imaging, magnetic resonance imaging) to investigate interindividual variability in tDCS response, according to associations between RT change and baseline fc, sc, attention, and E-fields. Although no effect of active versus sham tDCS was found overall, participants with lower theta or higher gamma default mode network connectivity and poorer attention at baseline showed greater response to tDCS. Higher E-fields were associated with greater response. No serious adverse effects occurred. A single tDCS session targeting dlPFC or IFG did not improve attention following pediatric ABI. We demonstrated how HD-EEG source-based connectivity may be used to personalize tDCS. Future research should explore whether personalization and/or repeated tDCS sessions can improve attention following pediatric ABI.